1995
DOI: 10.1128/mcb.15.7.3697
|View full text |Cite
|
Sign up to set email alerts
|

Characterization offus1ofSchizosaccharomyces pombe: a Developmentally Controlled Function Needed for Conjugation

Abstract: In Schizosaccharomyces pombe, the fus1 mutation blocks conjugation at a point after cell contact and agglutination. The cell walls separating the mating partners are not degraded, which prevents cytoplasmic fusion. In order to investigate the molecular mechanism of conjugation, we cloned the fus1 gene and found that it is capable of encoding a 1,372-amino-acid protein with no significant similarities to other known proteins. Expression of the fus1 gene is regulated by the developmental state of the cells. Tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
134
0
6

Year Published

1995
1995
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(146 citation statements)
references
References 71 publications
6
134
0
6
Order By: Relevance
“…The result was similar when the prm1D strain was h + and h 2 . The same kind of behavior was found for the dni1D, dni2D, and fus1D mutants (Petersen et al 1995; Clemente-Ramos Figure 7D, and data not shown). The sporulation efficiency of the unilateral WT 3 dni2D prm1D cross was significantly lower than that of the unilateral WT 3 dni2D and WT 3 prm1D crosses ( Figure 7D), suggesting that prm1 + and dni2 + acted in different genetic subpathways for cell fusion.…”
Section: Prm1 + and Dni + Genes Act In Different Subpathwayssupporting
confidence: 49%
See 2 more Smart Citations
“…The result was similar when the prm1D strain was h + and h 2 . The same kind of behavior was found for the dni1D, dni2D, and fus1D mutants (Petersen et al 1995; Clemente-Ramos Figure 7D, and data not shown). The sporulation efficiency of the unilateral WT 3 dni2D prm1D cross was significantly lower than that of the unilateral WT 3 dni2D and WT 3 prm1D crosses ( Figure 7D), suggesting that prm1 + and dni2 + acted in different genetic subpathways for cell fusion.…”
Section: Prm1 + and Dni + Genes Act In Different Subpathwayssupporting
confidence: 49%
“…The S. cerevisiae FUS1 and the S. pombe fus1 + genes have the same name and both mutants exhibit cell fusion defects during mating, leading to an accumulation of prezygotes (mating intermediates in which the mating partners have established a stable contact but have not yet fused). However, the corresponding proteins are not related; while Saccharomyces cerevisiae Fus1p is a membrane protein (Trueheart et al 1987), S. pombe Fus1p is a formin required for the organization of actin patches at the shmoo tip (Petersen et al 1995(Petersen et al , 1998b. S. pombe diploid nuclei are unstable, such that meiosis occurs immediately after karyogamy, and zygotes give rise to asci containing four ascospores (Nielsen 2004;Yamamoto 2004).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, there is a 71-amino-acid region within the carboxy-terminal domain that is highly conserved both with the formins and with a number of other proteins (see Fig. 4B (Petersen et al 1995), a genetically undefined S, cerevisiae ORF in GenBank, an Arabidopsis EST, a human EST, and a rice EST. This domain of similarity was independently identified by ourselves and S. Wasserman and has been named the FH2 domain (Castrillon and Wasserman 1994).…”
Section: Capu M R N a Is Present In The Germ Line And Soma During Oogmentioning
confidence: 99%
“…To identify gene products required for this process, we enriched for mutants of strain GP2640 (h 90 ade6-52 leu1-32 ura4-294 his3-D1 fus1TLEU2 rec12-152TLEU2) as follows. Haploid fus1 mutant cells are unable to mate and therefore cannot sporulate; however, fus1 mutant diploids, if heterozygous at the mating-type locus, are able to properly complete meiosis and sporulation (Petersen et al 1995). By coupling the ability of fus1D to prevent sporulation of haploid cells with the ability to selectively kill nonsporulated cells using glusulase treatment (Ponticelli and Smith 1989), the meiotic progeny of diploid cells can be efficiently selected.…”
Section: Methodsmentioning
confidence: 99%